The 3Rs in research: a contemporary approach to replacement, reduction and refinement. (30th October 2017) - MacArthur Clark, Judy
Abstract: First promulgated in 1959, the 3Rs of Replacement, Reduction and Refinement have evolved as fundamental principles underlying the use of animals and alternatives in science throughout the modern world. This review describes a contemporary approach to delivering the 3Rs through acknowledging the contribution of new technologies and emphasising that applying the 3Rs can be beneficial to good science as well as to animal welfare. This science-led approach moves the concept of the 3Rs out of an ethical silo where they were often considered by scientists to be an inconvenient obligation. On the contrary, relevant examples demonstrate the opportunity to practise better science using 3Rs technologies which deliver faster, more reproducible and more cost-effective results. Indeed, methods harnessing Replacement approaches may permit discoveries which are simply not feasible using animals and frequently are more flexible and agile since compliance with regulatory oversight requirements is simplified. Although the necessity for rigorous oversight is well recognised, it is important that the associated bureaucracy is not allowed to become prohibitive, causing scientists to avoid pursuing justifiable and important research involving animals. Public support for research is conditional – animals should not suffer unnecessarily and sufficient potential benefit should accrue from the research. However, society also actively seeks pioneering medical and scientific advances which can only be achieved through research. Therefore, a balance must be struck between safeguarding animal welfare whilst enabling high-quality science. It is this balance which promotes and sustains public confidence that animal based research is acceptable and being appropriately managed.